Editor's Foreword - Rynes, Sara L. (Academy of Management Journal, 2006)
The article discusses several topics that are featured in the following articles and columns. Several editors touch upon the subject of special issues forums in management journals and what their roles and impact are. The topic is of particular importance because the number of pages and space dedicated to these topics has grown considerably over the last twenty years. The results of the editors' research shows that many of these articles receive more citations than regular articles and helps expand author bases for many publications.